Pengaruh Online Customer Review, Online Customer Rating Dan Fitur Live Streaming Terhadap Keputusan Pembelian Produk Fashion Pada Marketplace Shopee Di Wilayah Surakarta - Isna Nur Riana; Tri Ratna Pamikatsih (FEB Universitas Maritim Semarang, 2024)
This study aims to determine the influence of online customer reviews, online customer ratings, and live streaming features on the purchase decisions of fashion products on the Shopee marketplace in the Surakarta region. This research was conducted in October 2023. The number of samples in this study was 147 respondents from Shopee users in Surakarta. Sampling is done using the purposive sampling method. The data collection technique used in this study is the quantitative method of distributing questionnaires online through social media. Multiple regression is the analysis method used in this study. The results of this study show that online customer reviews, online customer ratings, and live streaming features partially have a significant positive influence on the purchase decisions of fashion products in Surakarta.